Ectopic Cutaneous Schistosomiasis mansoni in the Sacral Region - Pedro Raso; Cibele Fontes Alves; Alexandre Tafuri; Wagner Luiz Tafuri (Karger Publishers, 2010)
The authors report one case of late cutaneous Schistosomiasis mansoni in a biopsy of a skin lesion in the sacral region in a 51-year-old female living in Contagem, Minas Gerais. The patient was treated successfully with oxamniquine (Mansil®).